Causalidade e gravidade das reações adversas ao benznidazol: influência dos níveis séricos do fármaco, do interferon Υ e do polimorfismo genético do fator regulador de interferon - Belmino, Alanna Carla da Costa (2022)
For the treatment of Chagas disease (CD) there are two drugs, Nifurtimox and Benznidazole (BNZ). The mechanism of action of BNZ consists in the formation of free radicals that can damage host cells, resulting in adverse drug reactions (ADR), which need to be studied in more detail for patient safety. Interferon gamma (IFN-y), in its turn, is a fundamental cytokine in the immune response to Trypanosoma cruzi, which may influence the symptomatic forms of CD and the response profile to drug therapy. This work aimed to study the causality and severity of ADRs to BNZ, as well as the influence of serum levels of the drug, IFN-y and the genetic polymorphism of the interferon regulatory factor (IRF). This is a prospective cohort study of patients with CD who underwent treatment with BNZ at the Chagas Disease Research Laboratory (LPDC). The evaluation of ADRs was performed at a mean of 30 and 60 days after the start of treatment and included clinical and laboratory analyses. ADRs were classified according to causality and severity. BNZ was quantified in serum by High Performance Liquid Chromatography. IFN-γ concentrations were determined in serum by enzyme immunoassay and the frequency of polymorphisms in the genes of interferon regulatory factors (IRF), IRF1 and IRF8, were performed using the Polymerase Chain Reaction. A high prevalence of ADRs was observed, most classified as possible and probable, of mild to moderate severity. It was possible to verify that the ADRs were not related to the serum concentrations of BNZ, but showed an association in relation to the serum levels of IFN- γ. Furthermore, serum IFN-γ levels were higher in patients with the digestive form and in those with the cardiac form, during and after treatment with BNZ. ADRs associated with interruption and interventions were those that affected the dermatological system, central and peripheral nervous system and sense organs such as ageusia. Mild hematological and biochemical alterations such as neutrophilia and lymphopenia were also observed. The adapted method for quantification of BNZ proved to be suitable for the quantification of BNZ in human serum. As for the polymorphism, the wild-type IRF8 genotype showed lower levels of IFN-γ, suggesting that the indeterminate form of the disease is more related to individuals without polymorphisms (wild gene) for IRF8. Despite the presence of several ADRs, BNZ is safe as long as the treatment is supervised by physicians and pharmacists. It is noted the importance of the service provided by the LPDC in the follow- up of patients promoting safe pharmacotherapy. Mechanisms that favor the predisposition to a specific clinical form of CD or the appearance of ADRs to BNZ are still unknown, but the results found with this work suggest the possibility that the knowledge of polymorphisms will help in the understanding of the pathology, improving the therapeutic direction in the future, requiring clinical studies to evaluate the frequencies of genetic polymorphisms and the concentrations of cytokines in the different stages of CD.